Regulatory effects of Auricularia cornea var. Li. polysaccharides on immune system and gut microbiota in cyclophosphamide-induced mice - Zhao, Ming; Shi, Wei; Chen, Xijun; Liu, Yanfang; Yang, Yan; Kong, Xianghui (Frontiers in Microbiology, 2022)
The immuno-regulating potential of edible fungus polysaccharides has gained more and more atten-tion. However, there is little information about the study of Auricularia cornea var. Li. polysaccha-rides regulating immunomodulatory activity. The objective of this work to analyze the immuno-modulatory activity and the mechanism of Auricularia cornea var. Li. polysaccharides supplementa-tion in an immunosuppressed mice model induced by cyclophosphamide. The effects of Auricularia cornea var. Li. polysaccharides on immune system including immune organ indices, immunoglobu-lin contents, and inflammation cytokines in immunosuppressed mice were determined. In addition, the regulatory effects of Auricularia cornea var. Li. polysaccharides on the gut microbiota and their metabolites were analyzed. Results showed that Auricularia cornea var. Li. polysaccharides signifi-cantly elevated immune organ indexes, remarkably enhanced the levels of IgA, IgG and IgM in se-rum and SIgA in the intestinal mucosa, conspicuously stimulated the levels of TNF-α, IL-1β, IL-4 and IL-10 in the serum. Auricularia cornea var. Li. polysaccharides also could restore gut microbio-ta to the pattern that is similar with that of the control group with increase of the relative abundanc-es of short-chain fatty acids (SCFAs)-producing bacteria. Furthermore, the content of SCFAs were increased after Auricularia cornea var. Li. polysaccharides supplementation. This study provides useful information for applications of Auricularia cornea var. Li. polysaccharides in immune-regulated foods and medicine.